The Role of Occupational Therapy in Managing Food Selectivity of Children with Autism Spectrum Disorder: A Scoping Review - Laura Reche-Olmedo; Laura Torres-Collado; Laura María Compañ-Gabucio; Manuela Garcia- (MDPI AG, 2021)
Food selectivity is common in children with autism spectrum disorder (ASD). It can be defined as the unwillingness to eat common or new foods, resulting in a lack of variety in the diet or limited food consumption for multiple reasons, such as inflexibility or sensory alterations. We conducted a peer scoping review to describe the interventions that are carried out from occupational therapy (OT) in children with ASD with food selectivity. Two authors independently searched the databases PubMed, Scopus, Web of Science, and EMBASE, as well as the OT journals indexed in Journal Citation Reports. Articles exploring OT interventions in children (≤12 years) with ASD and food selectivity, published in Spanish or English, with experimental design, and with full text available were included. Of the 1445 articles identified, 8 articles met the inclusion criteria. Three main intervention categories were identified: sensory-behavioral, family focused, and other interventions. Most of the interventions from OT were aimed at treating sensory-behavioral aspects. Only three articles described interventions led exclusively by occupational therapists, and the rest were led by a multidisciplinary team. Finally, although these interventions are not exclusive to OT, occupational therapists can participate together with other professionals as an essential component in the treatment of food selectivity in children with ASD.